O IMPACTO DA IDEOLOGIA CAPITALISTA NA ÉTICA DA PSICOLOGIA: DESAFIOS E CONTRADIÇÕES NA PRÁTICA PROFISSIONAL (REMUNOM, 2025)
This article aims to analyze the influence of capitalist ideology on ethics and professional practice in Brazilian psychology, questioning the extent to which the values ​​of the capitalist system permeate the work of psychologists and shape their social insertion. To this end, a qualitative study was conducted through a bibliographic review of scientific works and articles that discuss the relationships between psychology, ethics, ideology, and modes of production. The investigation is based on the assumption that capitalism interferes not only in the forms of economic production, but also in the constitution of subjectivities and professional practices. The results show that psychology often uncritically incorporates values ​​such as productivity, performance, and individualism, reproducing utilitarian logics that can undermine its ethical commitment to listening to and providing comprehensive care for the individual. In addition, there is a risk of the critical dimension of psychology being undermined, as it becomes more aligned with market imperatives than with the principles of social transformation and collective well-being. It is concluded that it is urgent to rethink the role of psychologists in light of an ethics committed to human rights, social criticism and resistance to the forms of oppression that are perpetuated under capitalist logic.